2016
DOI: 10.2355/isijinternational.isijint-2016-132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lanthanum on the Precipitation of NbC in Ferritic Steels

Abstract: The effect of lanthanum on the precipitation of NbC in ferritic steel has been studied within the experimental and theory methods. The diffusion coefficients of Niobium resulted from the diffusion couple experiment shows that Nb diffuses slightly faster in the presence of La than that in pure α-Fe. Using the first-principles calculations based on the density functional theory, we studied the interactions between any two defects of La, Nb and vacancy, as well as the variation of diffusion activation energies ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Despite the progress so far in RE alloying steel, the thorough theoretical study on the effect of RE on the precipitation of NbC is seldom detailed. The effect of lanthanum on the diffusivity of Nb and then the precipitation of NbC in ferritic steels was previously predicted and reported from our group [25].…”
Section: Introductionmentioning
confidence: 70%
“…Despite the progress so far in RE alloying steel, the thorough theoretical study on the effect of RE on the precipitation of NbC is seldom detailed. The effect of lanthanum on the diffusivity of Nb and then the precipitation of NbC in ferritic steels was previously predicted and reported from our group [25].…”
Section: Introductionmentioning
confidence: 70%
“…13) For the case of NbC precipitation in ferrite steels, our diffusion couple experiment reveals that Nb diffuses slightly faster in the presence of La, and consequently leads to the faster precipitation kinetics of NbC. 14) Despite the progress in RE containing steels research so far, it still remains to be investigated, since La generally cannot be detected directly in steels by conventional experimental methods due to its low solubility in steel. Although the advances in computational hardware and algorithms allow the application of first-principle calculations to the related investigation, it is beyond the capability of ab initio method in the case of precipitation and dissolution of NbC processes which involve long-ranged strain fields, long-ranged composition fluctuations and large numbers of atoms.…”
Section: Introductionmentioning
confidence: 94%
“…Through the utilization of the Kissinger method and analytical model calculations, it was demonstrated that the inclusion of rare earth Sm lowered the activation energy required for the formation of the θ ' precipitated phase, thereby promoting its formation. Employing the first‐principle calculation based on the density functional theory (DFT), Wang et al [ 24 ] conducted a systematically investigation into the impact of rare earth elements on the dissolution and precipitation behavior of niobium carbide in microalloy steel. Their findings indicated that the introduction of rare earth elements would change the solubility product of C and Nb in steel, reduce the activation energy required for NbC precipitation, enhance the diffusion coefficient of Nb within ferrite, and promote the precipitation of secondary phases.…”
Section: Introductionmentioning
confidence: 99%